Ion exclusion, osmoregulation and management of oxidative stress improve salt tolerance in rice at seedling stage - Mohanty, Ankita; Jena, Priyanka; Mondal, Subhankar; Bhaduri, Debarati; Chattopadhyay, Krishnendu; Chakraborty, Koushik (ORYZA-An International Journal of Rice, 2023)
Excess ion accumulation disturbs ionic homeostasis, creates an osmotic imbalance, and generates oxidative stress in plants under salinity stress. In the present experiment, the effect of salt stress at the seedling stage on the osmotic equilibrium and ROS scavenging potential was evaluated in ten differentially salt-sensitive rice genotypes. For this, the plants were grown hydroponically and salt stress equivalent to 12 dS m-1 was imposed at 3-4 leaf stages. The results showed that a few genotypes like FL478, AC41585, and AC39416A were able to maintain a lower Na+/K+ ratio in the leaf and thus proved more tolerant to salt stress than others. Additionally, these genotypes produced greater organic osmolytes (proline, glycine betaine, trehalose) and also had higher activities of key antioxidant enzymes (superoxide dismutase, catalase, peroxidase). On the contrary, Rashpanjor and CSR27 showed lesser ionic discrimination (higher leaf Na+/K+ ratio) but a moderate degree of salt tolerance, perhaps using Na+ effectively as an inorganic osmoticum to overcome stress. The susceptible genotypes like IR29 and Sabita were found extremely poor in restricting the upward movement of Na+, as well as the management of oxidative stress under saline conditions. From this study, we conclude that an efficient reactive oxygen species scavenging system along with greater osmotolerance helps to render salt tolerance at the seedling stage in rice.